2016
DOI: 10.1139/cjfr-2016-0137
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of mountain pine beetle outbreak on forest ecosystem services in western Canada

Abstract: After affecting millions of hectares of pine forests in western Canada, the mountain pine beetle (MPB; Dendroctonous ponderosae Hopkins) is spreading out of its native range and into Canada’s boreal forest. Impacts of outbreaks can be environmental, economic, and social, and an ecosystem services (ES) viewpoint provides a useful perspective for an integrated approach to assessing these impacts and may help to identify how possible management strategies could minimize these impacts. In this regards, a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 94 publications
0
33
0
Order By: Relevance
“…However, forest management practices before (e.g., fire suppression) and after (e.g., salvage logging) beetle attack may also play a vital role in the composition and size structure of understory and overstory species [33]. It is well established that structure and compositional development of salvage-logged (equivalent to clear cut) stands are significantly different from those of unsalvaged stands [32,44] as artificial regeneration with planting of nursery-grown tree seedlings is the basis of reforestation activity. In BC, nursery-grown tree seedlings such as lodgepole pine or hybrid spruce (Picea glauca Moench VossP icea engelmannii Parry) or subalpine fir (Abies lasiocarpa Hook.…”
Section: Stand Structure and Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, forest management practices before (e.g., fire suppression) and after (e.g., salvage logging) beetle attack may also play a vital role in the composition and size structure of understory and overstory species [33]. It is well established that structure and compositional development of salvage-logged (equivalent to clear cut) stands are significantly different from those of unsalvaged stands [32,44] as artificial regeneration with planting of nursery-grown tree seedlings is the basis of reforestation activity. In BC, nursery-grown tree seedlings such as lodgepole pine or hybrid spruce (Picea glauca Moench VossP icea engelmannii Parry) or subalpine fir (Abies lasiocarpa Hook.…”
Section: Stand Structure and Compositionmentioning
confidence: 99%
“…In unsalvaged stands, residual stand structure and composition play a vital role in development of the future forest [23,32,44]. Although the forests of central BC appear to have been devastated by the mountain pine beetle, studies of residual stand structure in many locations revealed that this was not the case for unsalvaged stands, as abundant residual green trees, regenerating saplings and seedlings of currently acceptable commercial tree species remain in the stands [51][52][53][54][55].…”
Section: Stand Structure and Compositionmentioning
confidence: 99%
See 3 more Smart Citations